2017
DOI: 10.1111/1471-0307.12408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium chelating agents on the solubility of milk protein concentrate

Abstract: The aim of this study was to determine the effects of calcium chelating agents on the dissolution and functionality of 10% (w/w) milk protein concentrate (MPC) powder. MPC powder dissolution rate and solubility significantly (P > 0.05) increased with addition of sodium phosphate, trisodium citrate (TSC) and sodium hexametaphosphate (SHMP), compared to MPC dispersions alone. Trisodium citrate and SHMP addition increased viscosity as a result of micelle swelling. However, dispersions containing SHMP showed a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 28 publications
2
37
1
Order By: Relevance
“…In addition to chelating calcium, SHMP can crosslink with casein proteins because of its 6 negative charges and homogeneous charge distribution. When SHMP is present in higher concentrations, it also forms calciumcasein phosphate complexes in the presence of calcium (McCarthy et al, 2017) as shown in Figure 1 (mechanism II). Understanding the role of calcium, caseins, and SHMP as a chelator improves our understanding of the changes in the physical and functional properties of high-protein dairy beverages.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to chelating calcium, SHMP can crosslink with casein proteins because of its 6 negative charges and homogeneous charge distribution. When SHMP is present in higher concentrations, it also forms calciumcasein phosphate complexes in the presence of calcium (McCarthy et al, 2017) as shown in Figure 1 (mechanism II). Understanding the role of calcium, caseins, and SHMP as a chelator improves our understanding of the changes in the physical and functional properties of high-protein dairy beverages.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the concentration of Ca 2+ , calcium-binding salts (CBS) such as salts of phosphoric and citric acids can be added prior to processing to increase heat stability and reduce fouling (Lewis, 2011). The effects of CBS addition on protein structure and heat stability have been studied in various types of milk systems (Vujicic, de Man, & Woodrow, 1968), milk protein concentrate dispersions (McCarthy et al, 2017;Mizuno & Lucey, 2005), milk microfiltration concentrates (Toledo Renhe, Indris, & Corredig, 2018), concentrated micellar casein dispersions (De Kort, Minor, Snoeren, Van Hooijdonk, & Van der Linden, 2011 Furuichi, 1975), individual caseins (Guo, Campbell, Chen, Lenhoff, & Velev, 2003), soymilk (Pathomrungsiyounggul, Lewis, & Grandison, 2010), reconstituted calciumfortified milk powders (Williams, D'Ath, & Augustin, 2005) and whey protein beverages fortified with calcium (Keowmaneechai & McClements, 2002& 2006.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a group of researchers have reported that conjugation of WPI with maltodextrin at 60 °C for 24 h enhanced the protein solubility at pH 3.5–4 (McCarthy et al . ). Interestingly, the system did stabilise when SHMP concentration was increased to 1% w/w.…”
Section: Resultsmentioning
confidence: 97%
“…However, these proteins are prone to denaturation and thus subsequent aggregation upon heating, arising from conformational changes due to alterations in the degree of exposed hydrophobic regions, as well as modification of protein charge (McCarthy et al . ). It is stated that heat treatment at 70–75 °C leads to the formation of small and reversible bonds between protein particles via weak van der Waals interactions while higher temperatures (80–90 °C) strengthen the covalent disulphide bonds.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation